Strategies for ensuring sustainable democracy in South Africa - Victor G. Hilliard; Mxolisi Notshulwana (Acta Academica, 2001)
This article examines the South African experience of democracy and focuses in particular on the democratisation of South Africa’s government and administration. The democratisation process has not been problem-free. The tone was set by the negotiation of the 1993 Interim Constitution Act, and later the promulgation of a 1996 Constitution Act. Both these Constitution Acts made provision for a host of human rights and for a democratic dispensation intended to function in a multiparty context. To promote sustainable democracy, and to ensure that the majority of constitutional principles are upheld as far as possible, various checks and balances have to be built into the South African governmental system. It is essential that all public functionaries be accountable for their actions and/or lack thereof. This article examines some of the mechanisms or strategies to keep democracy vibrant and to ensure that public functionaries serve the general good, and do not pursue selfish, parochial interests.